STATUS MUTU AIR SUNGAI BANYU IRANG DI DESA BANYU IRANG, KECAMATAN BATI-BATI, KABUPATEN TANAH LAUT. Water Quality Status Of The Banyu Irang River In Banyu Irang Village, Bati-Bati Sub District, Tanah Laut District - Fadillah, Muhammad Rizqan; Fatmawati, Fatmawati; Fauzana, Noor Arida; Badaruddin, Badaruddin (Universitas Lambung Mangkurat, 2024)
Banyu Irang River water quality status Banyu Irang Village, Bati-Bati District, Tanah Laut Regency, South Kalimantan Province due to domestic waste into these waters is unknown. The purpose of this study was to analyze the quality status of the Banyu Irang River water. Determination of river water quality status is approached by study methods based on KepmenLH. No. 115 of 2003 concerning Guidelines for Determining Water Quality Status. Measurement and sampling of water quality was carried out on March 5, 2024 as many as 4 points in the waters of the Banyu Irang River and 2 points in the waters of the Bangkal Kacil river with 10 water quality parameters (temperature, brightness, TSS, pH, DO, BOD, BOD, COD, Ammonia, Oil and fat as well as total coliform) using the surface water sampling method according to SNI 6989.57: 2008, then analyzed in the BBTKL-PP Banjarbaru laboratory with the method in accordance with the parameters measured and analyzed. Determination of water quality status using the Storet method, both from the results of comparisons with BMAN according to PPRI No.22 of 2021 and Pergub. Kal -Sel No.05 of 2007 shows that the water quality status of the Banyu Irang River is obtained - 45, designated as class D: Bad, score ≥ - 31, severe turmoil, because some of the parameters measured and analyzed do not meet the quality standards, such as The DO parameters are below the required minimum levels and COD, oil and fat and high total coliforms, exceeding the maximum level required.